The Characteristics of Yoghurt Enriched with Pumpkin Seed Filtrate - Rizal, Dinda Dwifa; Slamet, Agus; Kanetro, Bayu (Indonesian Journal of Food Technology, 2025)
This study aimed to investigate the effect of adding pumpkin seed filtrate and starter concentration on the characteristics and acceptability of yoghurt. The research employed a Completely Randomized Design with two factors: filtrate concentration (3, 6, and 9%) and starter concentration (3, 5, and 7%). The parameters analyzed included sensory acceptance, viscosity, pH, total acidity, moisture content, ash content, protein content, phosphorus content, antioxidant activity, and total lactic acid bacteria. The results showed that the addition of pumpkin seed filtrate and starter significantly affected the chemical and microbiological characteristics of the yoghurt but had no significant effect on sensory acceptance. The best yoghurt was obtained from the combination of 9% filtrate and 3% starter, with a viscosity of 1,220 cP, pH of 3.63, acidity of 1.27%, protein content of 3.90%, phosphorus content of 161.28 mg/100 mL, antioxidant activity of 10.64% RSA, and, and total lactic acid bacteria count of 2.69 × 10⁹ CFU/g.